Beehelp: um aplicativo para compartilhamento de informações de estabelecimentos de saúde baseado em ciência de contexto - Santos, Marcelo Luis dos (Universidade do Vale do Rio dos Sinos, 2016)
With the popularization of mobile devices, many new app’s have been created to attend specific areas of the market and new concepts like context awareness and social collaboration often have grown to provide smarter and easier to use applications. This paper introduced a solution which joins these three concepts in health area. The proposed model provides information about health establishments based on context awareness and enables interaction among users through social networks. A mobile application was created and it was validated by users using a test script with the objective of evaluate its effectiveness, efficacy and use satisfaction. The results of the test script show indexes higher than 70% in usability evaluation and users opinion about the app’s utility, showing that it instigates the users interest to use it and to share information about health establishments. These information are very important to people and it could be crucial to the users when they are searching for some health establishment, manly in locations that doesn’t have good health services.
Keywords: Computação móvel; Sensibilidade ao contexto; Redes sociais; Geolocalização; Estabelecimento de saúde; Mobile computing; Context awareness; Social networks; Geolocation; Health establishments